Neo-liberalism and the Architecture of the Post Professional Era (The Urban Book Series,, 2018)
This book discusses the effects of Neo-Liberal policies on the transformations of architectural and urban practices and education in the transition from the era of "professionalism" to "post-professionalism." Building on previous literature in the field of contemporary theory of architecture, it provides the necessary resources for the study of contemporary architecture and urban politics, urban sociology, local administration and urban geography. Further, it develops a political and critical perspective on contemporary practices of architecture and urbanism, their implementation, legal background, political effects and social results. The book will interest readers from a wide range of academic disciplines, from political science to architecture, and from urban studies to sociology.